Diversity analysis of microbial communities in broiler ceca. - Muhammad Rumman Aslam (22683482) (2025)
(A) metrics (Shannon diversity, Simpson diversity, evenness, and richness) across three groups (BSFL, plant oils, and animal fats); (B) alpha diversity metrics for eight diets featuring various fat sources. BSFL – basal diet with 100% black soldier fly (Hermetia illucens) larval fat; plant oil diets (SO – basal diet with 100% soybean oil; RO – basal diet with 100% rapeseed oil; PO – basal diet with 100% palm oil; PKFD – basal diet with 100% palm kernel fat distillate); animal fats (PF – basal diet with 100% poultry fat; PL – basal diet with 100% pig lard; BT – basal diet with 100% beef tallow).